Pacific American Fisheries cannery at Port Moller, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: P.A.F. Cannery, Port Moller, Alaska PH Coll 247.903 Port Moller is a village in southwest Alaska. It is located on the Alaska Peninsula at the entrance of Port Moller Inlet (20 mi long) of Bristol Bay on the Bering Sea. Primary industries are fishing and fish canning.